Editorial: Expanding Arts and Physical Educational Discourses and Boundaries - Ove Østerlie; Sofia Jusslin (Journal for Research in Arts and Sports Education)
This issue of JASEd brings together five contributions that critically examine the evolving discourses within music education, physical education, outdoor education, and aquatic education. Despite their distinct thematic focuses, these studies share a common interest in questioning traditional paradigms and expanding the conceptual and methodological frameworks that underpin arts and physical education. Below, we recap each contribution and highlight the overarching theme that binds them together.